Femoral–tibial contact stresses on fixed rotational femur models - Yuwen, Peizhi; Sun, Weiyi; Guo, Jialiang; Chang, Wenli; Wei, Ning; Wang, Haicheng; Ding, Kai; Chen, Wei; Zhang, Yingze (Frontiers in Surgery, 2023)
Objectives: This study aims to quantitatively evaluate the femoral-tibial contact pressure on the knee under certain malrotaional degrees. Methods: Femoral-tibial contact pressure was carried out on fourteen fixed rotational knee models under 200/400/600 N vertical load using ultra-low-pressure sensitive film technology, rotation angles including neutral position (0°, anatomically reduced), 5°, 10°, 15° internally and externally. Data were collected and analyzed with SPSS software. Results: There are significant statistical differences between the medial contact pressure among rotational deformities (including neutral position) (P<0.01), the increase in the degree of fixed internal malrotation of the femur resulted in a linear increase in the medial femoral-tibial contact pressures (P<0.05) under 200/400/600 N vertical load, while increase in the degree of fixed external malrotation resulted in a linear decrease(P<0.05). Except the 200N compression, we can’t find significant differences in lateral contact pressures (P>0.05). In the comparison of medial to lateral contact pressures, no statistically significant differences were found in neutral and 5° internal rotation under 200/400N, neutral, 5° internal rotation and 15° external rotation under 600N. In contrast, medial contact pressures were higher than lateral at other angles (P<0.05). Conclusion: Obvious contact pressure changes were observed in rotatory femur. Doctors should detect rotational deformity as much as possible during operation and perform anatomical reduction. For patients with residual rotational deformities, indication of osteotomy should not be too broad.